COVID-19: Training considerations: List of training advices & precautions by the co-president of the club of sport cardiologists (France) & associated sports medicine doctors - Chevalier, L.; Blanchard, S.; Dusfour, B. (2020)
Many athletes can be infected without knowing it, with little or no symptoms at rest. They are, however, likely to suffer from severe exercise-related heart problems if they do not follow the following simple advice